Research on Application Value of Computer Software Development in Java Programming Language - Jiang, Yangyang (Journal of physics. Conference series, 2020)
After the industrial revolution, the level of productivity has greatly improved, and the social economy has developed rapidly. At the same time, science and technology have also made rapid progress under the economic drive. As a product of modern science and technology, the Internet has made an indelible contribution to human society. In this context, the Java programming language based on computer software development has also entered people's field of vision, and has received widespread attention. This article is to briefly introduce some of the origins, characteristics and main applications of the Java programming language in people's production and life.